Zero Trust Network Architecture Design For Mid-Scale Organizations - Kamila, Nurul; Makhsun; Sudarno (Universitas Mohammad Husni Thamrin, 2026)
The development of information technology, the adoption of cloud-based services, and the implementation of remote work patterns increase network security risks in medium-sized organizations. Traditional network security approaches that focus on the perimeter are considered no longer adequate in facing increasingly complex cyber threats. This study presents the design of a Zero Trust Network (ZTN) architectural blueprint specifically designed for medium-sized organizations. The research method used is a conceptual approach through literature review, network security requirements analysis, and the design of the ZTN logical architecture. The research results are a Zero Trust Network architectural blueprint that emphasizes continuous verification, identity-based access control, and the application of the principles of least privilege and micro-segmentation. The architectural design is arranged in a modular and phased manner and is aligned with the NIST SP 800-207 framework, so it remains realistic for adoption without requiring drastic infrastructure changes. The resulting ZTN architectural blueprint can be used as an initial reference for medium-sized organizations in designing a Zero Trust-based network security strategy. This research is conceptual in nature and does not include the implementation stage or empirical testing in a real operational environment. It is hoped that the results of this study can serve as an initial reference for medium-sized organizations in designing a more adaptive and sustainable network security strategy.